Apigenin suppresses the stem cell-like properties of triple-negative breast cancer cells by inhibiting YAP/TAZ activity - Li, Ying-Wei; Xu, Jian; Zhu, Guo-Yuan; Huang, Zhu-Juan; Lu, Yan; Li, Xian-Qian; Wang, Neng; Zhang, Feng-Xue (Cell death discovery, 2018)
Triple-negative breast cancer (TNBC) remains a clinical challenge because of the absence of effective therapeutic targets. In TNBC, overexpression of YAP and TAZ correlates with bioactivities of cancer stem cells (CSCs), high histological grade, resistance to chemotherapy, and metastasis. Thus, YAP/TAZ may serve as potential therapeutic targets in TNBC. To identify YAP/TAZ inhibitors, in previous experiments, we screened a library of natural compounds by using YAP/TAZ luciferase reporter assay and identified apigenin as a potential inhibitor. In this study, we demonstrated that apigenin significantly suppressed the proliferation and migration of TNBC cells. Furthermore, we demonstrated that apigenin inhibited stemness features of TNBC cells in both in vitro and in vivo assays. Our mechanism study demonstrated that apigenin decreased YAP/TAZ activity and the expression of target genes, such as CTGF and CYR61, in TNBC cells. We also showed that apigenin disrupted the YAP/TAZ-TEADs protein–protein interaction and decreased expression of TAZ sensitized TNBC cells to apigenin treatment. Collectively, our studies suggest that apigenin is a promising therapeutic agent for the treatment of TNBC patients with high YAP/TAZ activity.